Resepsi dan Transmisi Pengetahuan dalam Film Papi dan Kacung Episode 8-11: Sebuah Kajian Living Hadis - Ihsan Nurmansyah (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This paper discusses the study of living hadith in the film Papi dan Kacung (read: PdK) episodes 8-11 uploaded by Qorryan on Instagram in 2019. The film PdK is a short film of Islamic nuances which in each scene shows a reception from the hadith The Prophet, especially things that are forbidden. Therefore, to find out the variety of receptions on the Prophet's hadith in the film PdK episodes 8-11 using reception theory and knowledge transmission. The results of this study are 1) first, the exegetical reception was manifested in the reading of the Book Riyadhus Shalihin; second, the aesthetic reception contained in the reading of the Book Riyadhus Salihinaccompanied by Zamzam backsound; third, functional receptions on the informative aspect, namely a ban resembling the opposite sex, a ban on doing the three things that are hated by God, a ban on disparaging goodness and a prohibition on cursing. Whereas the function in the performative aspect, namely Kacung always follows the advice of his father in the form of asking forgiveness, taking off the earrings he wears, giving good advice to his friends and giving a smile. 2) As for the transmission of knowledge in the film